2016
DOI: 10.1002/2016jd024969
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Actual impacts of deforestation and afforestation on land surface temperature

Abstract: Forests are undergoing significant changes throughout the globe. These changes can modify water, energy, and carbon balance of the land surface, which can ultimately affect climate. We utilize satellite data to quantify the potential and actual impacts of forest change on land surface temperature (LST) from 2003 to 2013. The potential effect of forest change on temperature is calculated by the LST difference between forest and nearby nonforest land, whereas the actual impact on temperature is quantified by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
110
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(137 citation statements)
references
References 63 publications
(138 reference statements)
12
110
0
1
Order By: Relevance
“…Zhao and Jackson 2014;Li et al 2015;Peng et al 2014;Duveiller et al, 2018b). Both appear to yield similar results (Li et al, 2016), but the space-for-time approach allows Earth Syst. Sci.…”
Section: Introductionsupporting
confidence: 52%
“…Zhao and Jackson 2014;Li et al 2015;Peng et al 2014;Duveiller et al, 2018b). Both appear to yield similar results (Li et al, 2016), but the space-for-time approach allows Earth Syst. Sci.…”
Section: Introductionsupporting
confidence: 52%
“…The increase in soil moisture for forests tends to increase the surface heat capacity, which results in increases in daytime heat storage and nighttime heating. In addition, due to the higher ET from forests relative to open land, the increases in air humidity and boundary layer clouds increase the downward longwave radiation from the atmosphere and decrease the upward longwave radiation from the surface, which increases surface temperatures at night [9,15,17].…”
Section: Discussionmentioning
confidence: 99%
“…There are two kinds of observations, that are widely used to explore the effects of forests on temperature: satellite and in-situ data [7,14,[17][18][19][20]. Some studies used satellite observations found that afforestation in China cooled daytime temperatures and warmed the nocturnal temperatures [18,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the estimated RF induced by LUCC is far less than those of other anthropogenic forcings (e.g., well‐mixed greenhouse gases) at a global scale, the climatic impacts of LUCC at local to regional scales can be comparable to or even larger than the impacts from these forcing agents (Chase et al, ; Gao et al, ; Lee et al, ; Lohila et al, ; Pitman & Zhao, ; Zhao & Pitman, ). A number of observational and modeling studies have demonstrated that the historical LUCC (i.e., deforestation) could generally yield to a cooling effect on the mean temperature in high‐latitude regions but a warming effect in tropical regions (e.g., Bala et al, ; Betts, ; Claussen et al, ; Devaraju et al, ; Lee et al, ; Y. Li et al, , ; Zhang et al, ). However, uncertainties (e.g., disagreements in magnitude and sign) in the LUCC‐induced mean temperature changes still remain in multimodel results.…”
Section: Introductionmentioning
confidence: 99%